Galactomanana reticulada de sementes de peltogyne confertiflora: uma eficiente matriz cromatográfica de afinidade para isolar lectinas galactose-ligantes - Ferreira, Francisco Valdicélio (2021)
Galactomannans constitute the largest group of polysaccharides with energy reserve capacity in the endosperm of seeds, especially those belonging to the Leguminosae family, having several industrial applications. However, valuing bioprospecting in the sense of exploring biodiversity allows the protagonist and discovery of natural compounds with potential applications. However, valuing bioprospecting in the sense of exploring biodiversity favors scientific protagonism and the discovery of natural compounds with potential applications. In this context, the search for news chromatographic matrices for protein isolation makes galactomannans attractive and new plant sources for obtaining these molecules have been researched. Thus, the present work aimed to evaluate the efficiency of reticulated galactomannan from seeds of Jatobá-de-brinco (Peltogyne confertiflora) as an affinity chromatographic matrix for galactose-binding lectins purification. First, galactomantan was extracted from the P. confertiflora seeds for physicochemical characterization, crosslinking tests and preparation of chromatographic matrices. Then, the crosslinked galactoman matrices were used in the purification of jacalin, frutalin, abrin, pulchellin and ricin lectins, later analyzed the integrity, purity, yield and bioactivity of these proteins. The extracted galactomannan showed an average yield of 59.6 mg per gram of seed flour. Furthermore, galactamannan presented physicochemical characteristics and structural stability similar to those of other plant galactomannans. The Gal/Man ratio of galactoman evaluated by 1H and 13C NMR spectra was 1.00/1.14 and 1.00/1.09, respectively. The cross-linked galactomannan matrix was able to isolate all tested lectins, which in addition to showing integrity and purity, were also bioactive. Finally, it can be concluded that P. confertiflora seeds are an excellent source for obtaining galactomannan and that the potential use of polysaccharides as a biotechnological product for the purification of biomolecules can contribute to the enhancement of natural resources in the brazilian semiarid region, adding value to your products.